“The Penny Drops”: Investigating Insight Through the Medium of Cryptic Crosswords - Friedlander, Kathryn J.; Fine, Philip A. (Frontiers in Psychology, 2018)
A new protocol for eliciting insight (’Aha!’/Eureka) moments is proposed, involving the solving of British-style cryptic crosswords. The mechanics of cryptic crossword clues are briefly explained, and the process is set into the insight literature, with parallels being drawn between several different types of cryptic crossword clues and other insight-triggering problems such as magic, jokes, anagrams, rebus and remote association puzzles (RAT), as well as ‘classic’ thematic or spatial challenges. We have evidence from a previous survey of cryptic crossword solvers that the ‘Aha!’ moment is the most important driver of continued participation in this hobby, suggesting that the positive emotional ‘payback’ has an energizing effect on a participant’s motivation to continue solving. Given the success with which a good quality cryptic crossword elicits ‘Aha!’ moments, cryptics should prove highly valuable in exploring insight under lab conditions. We argue that the crossword paradigm overcomes many of the issues which beset other insight problems: for example, solution rates of cryptic crossword clues are high; new material can easily be commissioned, leading to a limitless pool of test items; and each puzzle contains clues resembling a wide variety of insight problem types, permitting a comparison of heterogeneous solving mechanisms within the same medium. Uniquely among insight problems, considerations of expertise also come into play, allowing us to explore how crossword solving experts handle the deliberate misdirection of the cryptic clue more effectively than non-expert, but equally experienced, peers. Many have debated whether there is such a thing as an ‘insight problem’ per se: typically, problems can be solved with or without insight, depending on the context. We argue that the same is true for cryptic crosswords, and that the key to the successful triggering of insight may lie in both the difficulty of the challenge and the degree to which misdirection has been used. Future research is outlined which explores the specific mechanisms of clue difficulty. This opens the way to an exploration of potential links between solving constraints and the experiencing of the ‘Aha!’ moment, which may shed light on the cognitive processes involved in insight solution.